IMPACT OF SHIFT PATTERN ON OPTIMAL HUMAN RESOURCE MANAGEMENT STRATEGY: AN OPTIMISATION APPROACH - Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2023)
Today, human resource management plays an increasingly important role, as both production and service activities require a large number of employees, so an optimal human resource management strategy can have a direct impact on the efficiency of the production and service process. Within the frame of this article, a new approach is described, which focuses on the scheduling of employees having different shift patterns. The numerical analysis of different scenarios shows the impact of the scheduling on the number of required employees and the total cost of human resources.